Exile, Non-Belonging and Statelessness in Grangaud, Jabès, Lubin and Luca: No man’s language - Kerr, Greg (Comparative Literature and Culture, 2021)
At least since the Romantic era, poetry has often been understood as a powerful vector of collective belonging. The idea that certain poets are emblematic of a national culture is one of the chief means by which literature historicizes itself, inscribes itself in a shared cultural past and supplies modes of belonging to those who consume it. But what, then, of the exiled, migrant or translingual poet? How might writing in a language other than one’s mother tongue complicate this picture of the relation between poet, language and literary system? What of those for whom the practice of poetry is inseparable from a sense of restlessness or unease, suggesting a condition of not being at home in any one language, even that of their mother tongue? These questions are crucial for four French-language poets whose work is the focus of this study: Armen Lubin (1903-74), Ghérasim Luca (1913-94), Edmond Jabès (1912-91) and Michelle Grangaud (1941-). Ranging across borders within and beyond the Francosphere – from Algeria to Armenia, to Egypt, to Romania – this book shows how a poetic practice inflected by exile, statelessness or non-belonging has the potential to disrupt long-held assumptions of the relation between subjects, the language they use and the place from which they speak.